Práticas de letramento e pessoalidades em um curso de pré-vestibular popular: um estudo de caso - Andreza Barroso Gonçalves (2022)
This case study looks into the relations between literacy practices and personhood built by participants (students, coordinators and teachers) in a popular preparatory course part of Educafro Minas Gerais chain, the branch Educafro Aimorés. I aim at responding to the following questions: how are the literacy practices built by the participants in the observed social environment? What is it like to be an Educafro student? How is an Educafro student prepared for Enem? How are issues such as personhood and identities approached as possibilities to coordinators, teachers and students to think about who they are and their participation in literacy events? In order to answer these questions, we considered the theoretical background of literacy as social practice (LPS) (STREET, 1984, 2017), the concepts and theoretical models of ideological and autonomous literacy, literacy events, (HEATH, 1982; STREET, 2000; 2012) literacy practices (STREET,1995-2014), the studies on academic literacy (LEA; STREET, 1998; LILLIS; SCOTT, 2007) as well as the concept of personhood (EGAN-ROBERTSON, 1998; BLOOME et al., 2005; STREET, 2007), which on thesis, was also thought from the possibilities of being and acting in the world. The investigation approach chosen was built from an ethnographic perspective (GREEN, DIXON, ZAHARLIC, 2007; BLOOME, 2012). The data production was developed through participant observation, involving several levels of participation of the researcher, times as an observer, times as a more active participant, times assuming the role of a teacher in one of the subjects. The database contains registers of field notes, audio interviews with teachers and students, audio and video of classes from the following curricular subjects: essay writing, Portuguese language and literature, social and physical geography, biology, physics, mathematics, history, Spanish, literature and blackness, culture and citizenship (NCC), which is specific of Educafro Minas and it represents the values tripod that guides the education actions of this institution. From the identification of a rich point (AGAR, 1986, 1999), it was decided to analyze what characterizes, on the branch Educafro Aimorés participants’ perspective, to think education in a different way. I took as an analytical starting point the literacy event, Opening class, that enabled the evaluation of other three events: the first physics and Portuguese language and literature classes and the second literature class. The analyses of these events, yet exploitative, showed, among other things, how literacy practices and personhood built in this space join themselves to cultural themes, such as ethno-racial relations, blackness, self management or two-way volunteering, social space notion. The different literacy practices, the different personhood and the different identities observed from the analysis of interactions among branch participants revealed the emancipating, revendicating, affirmative nature of the important political actor which is Educafro, that has educated people in a critical, thoughtful and political way, besides preparing students to Enem exam.